2024
DOI: 10.1029/2023jc019685
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Coastal‐Ocean Pathways of Land‐Sourced Contaminants in the Aftermath of Hurricane Florence

Melissa Moulton,
Joseph B. Zambon,
Z. George Xue
et al.

Abstract: Extreme precipitation during Hurricane Florence, which made landfall in North Carolina in September 2018, led to breaches of hog waste lagoons, coal ash pits, and wastewater facilities. In the weeks following the storm, freshwater discharge carried pollutants, sediment, organic matter, and debris to the coastal ocean, contributing to beach closures, algae blooms, hypoxia, and other ecosystem impacts. Here, the ocean pathways of land‐sourced contaminants following Hurricane Florence are investigated using the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
0
0
Order By: Relevance
“…For example, local plants and wastewater treatment facilities, as well as any untreated or contaminated water found in waterways or local water sources such as lakes, rivers, or bayous, can contaminate rain or flood water. Evidence of this can be found in atmospheric dispersion studies, where biological contaminants such as Legionella were found at various locations due to wind travel; this was also the case with land sourced contaminants after hurricanes due to wind driven rain [37,38]. During severe storms, tornados, or hurricanes, power outages cause the loss of a building's main function, which is interior environment climate control.…”
Section: Outdoor Environmental Conditionsmentioning
confidence: 92%
“…For example, local plants and wastewater treatment facilities, as well as any untreated or contaminated water found in waterways or local water sources such as lakes, rivers, or bayous, can contaminate rain or flood water. Evidence of this can be found in atmospheric dispersion studies, where biological contaminants such as Legionella were found at various locations due to wind travel; this was also the case with land sourced contaminants after hurricanes due to wind driven rain [37,38]. During severe storms, tornados, or hurricanes, power outages cause the loss of a building's main function, which is interior environment climate control.…”
Section: Outdoor Environmental Conditionsmentioning
confidence: 92%